2017
DOI: 10.19044/esj.2017.v13n21p44
|View full text |Cite
|
Sign up to set email alerts
|

Résultats De 5ans De Thyroïdectomie Au Service D’orl Et Chirurgie Cervico-Faciale De l’Hôpital National De Niamey (Niger)

Abstract: Purpose: To evaluate the results of thyroidectomy in the Oto-RhinoLaryngology and Neck Surgery office of the National Hospital of Niamey in Niger. Materials and methods: we analyzed the epidemiological aspects, the indications, the technics and the evolution of thyroidectomy through a retrospective and descriptive study conducted from January 2010 to December 2015. Results: Thyroidectomy represents 8, 51% (n = 236/2773) of the ENT operative activities and an average of 47.2 cases per year for 5 years. Among th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
0
0
Order By: Relevance
“…a rate of 26.6%, while in Niger, Illé S and coll. [10] performed 236 cases of thyroidectomy over the same period with a rate of 8.51%. In Senegal, a rate of 8.51% was found by Diédhiou D. et al [11], while in the Central African Republic, Poumale F. et al…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…a rate of 26.6%, while in Niger, Illé S and coll. [10] performed 236 cases of thyroidectomy over the same period with a rate of 8.51%. In Senegal, a rate of 8.51% was found by Diédhiou D. et al [11], while in the Central African Republic, Poumale F. et al…”
Section: Discussionmentioning
confidence: 99%
“…In Niger, Illé S et al reported that the indications for operation were dominated by multi-nodular or thyroid goiters presenting functional problems (39% of cases), followed by goiters suspected of malignancy (35% of cases), simple goiters came in third position (18% of cases). case) [10]. In Senegal, Diédhiou D. et al had found that toxic goiters constituted the cause of thyroidectomy [11], while in the Central African Republic, goiters suspected of malignancy came first [12].…”
Section: Discussionmentioning
confidence: 99%